The Role of Leader in Fostering Village Government Administration in the Hila Village Leihitu Subdistrict Central Maluku Regency Maluku Province - Hendry Selanno (ARISTO, 2020)
The purpose of this study was to find out the role of leader  in fostering government administration in the Hila Village, Leihitu Subdistrict, Central Maluku Regency. This has an important connection with public service where he role according to Katz and Kahn, Role is a dynamic aspect of status. If someone carries out their rights and obligations according to their position, he / she carries out a role. The method used in this research is descriptive qualitative. Data collection techniques in this study were observation and interview techniques. The informants in this study were 8 people consisting of sub-district office staff and village officials. This research data was analyzed by using the stages of data collection, data reduction, data presentation, and conclusions drawing or data verification. The results of this study indicated that the role of Leader in fostering village government administration in the Hila village, Leihitu District, Central Maluku Regency had not been yet maximal based on Government Regulations No. 17 of 2018 concerning the Subdistrict, namely: Through Guidance, Supervision, Consultation and Facilitation. The conclusion, the Leader was less aware of his responsibilities in fostering village government administration. For this reason, it is expected that the Leader of Leihitu must carry out his functions and roles to the maximum extent possible in fostering Village Government Administration in the village Hila village, Leihitu District, Central Maluku Regency.